A simple clinical score to stratify the risk of procedure-related adverse events in ERCP procedures with trainee involvement - Voiosu, Theodor A.; Benguș, Andreea; Bronswijk, Michiel; Lyutakov, Ivan; Klarin, Ivo; Voiosu, Bianca; Bălănescu, Paul; Diaconu, Claudia; Busuioc, Bogdan; Boskoski, Ivo; Voiosu, Andrei M.; Mateescu, Radu B.; Wani, Sachin (Endoscopy, 2023)
Background Optimal training strategies in endoscopic retrograde cholangiopancreatography (ERCP) remain controversial despite the shift toward competence-based training models, with limited data available on patient safety during training. We aimed to assess whether pre-procedural clinical predictors could identify patients at low risk of developing procedure-related adverse-events (AEs) in a training environment.Methods We performed a prospective, multicenter, cohort study in five training centers. A data collection system documenting indication, clinical data, trainee performance (assessed using a validated competence assessment tool), technical outcomes, and AEs over a 30-day follow-up was utilized. We developed a clinical risk score (Trainee Involvement in ERCP Risk Score [TIERS]) for patients undergoing ERCP and compared the rate of AEs in a training environment between low-risk and high-risk groups. The association between trainee performance and AE rate was also evaluated.Results 1283 ERCPs (409 [31.9 %, 95 %CI 29.3 %–34.4 %] with trainee involvement) performed by 11 trainers and 10 trainees were analyzed. AEs were more frequent in the high-risk compared with the low-risk group: 26.7 % (95 %CI 20.5 %–34.7 %) vs. 17.1 % (95 %CI 12.8 %–22.2 %). TIERS demonstrated a high negative predictive value for AEs (82.9 %, 95 %CI 79.4 %–85.8 %) and was the only predictor of AEs on multivariable analysis (odds ratio 1.38, 95 %CI 1.09–1.75). Suboptimal trainee performance was associated with an increase in AE rates.Conclusion Simple, clinical-based predictive tools could improve ERCP training by selecting the most appropriate cases for hands-on training, with the aim of increasing patient safety.